2019
DOI: 10.1016/j.geomphys.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Locally conformally symplectic convexity

Abstract: We investigate special lcs and twisted Hamiltonian torus actions on strict lcs manifolds and characterize them geometrically in terms of the minimal presentation. We prove a convexity theorem for the corresponding twisted moment map, establishing thus an analog of the symplectic convexity theorem of Atiyah and Guillemin-Sternberg. We also prove similar results for the symplectic moment map (defined on the minimal presentation) whose image is then a convex cone. In the special case of a compact toric Vaisman ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The above formula (3) shows that Vaisman metrics have potential, and by (1), if (Ω, θ) is an lcK structure with potential h, then (e f Ω, θ + df ) is an lcK structure with potential e f h. Remark 2.3. Every lcK metric with potential, in particular every Vaisman metric, on a compact complex manifold is strict.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The above formula (3) shows that Vaisman metrics have potential, and by (1), if (Ω, θ) is an lcK structure with potential h, then (e f Ω, θ + df ) is an lcK structure with potential e f h. Remark 2.3. Every lcK metric with potential, in particular every Vaisman metric, on a compact complex manifold is strict.…”
Section: Introductionmentioning
confidence: 97%
“…These lcK structures, however, have the same Lee vector field as the Vaisman structures. More recently, F. Belgun [1] constructed examples of lcK manifolds with holomorphic Lee vector field on compact complex manifolds which are not of Vaisman type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [I17], we showed that any compact toric LCK manifold admits a toric Vaisman metric. Finally, in [BGP19], Belgun, Goertsches and Petrecca studied the moment map of a certain class of toric LCS manifolds and showed a corresponding convexity property.…”
Section: Introductionmentioning
confidence: 99%
“…Belgun-Goertsches-Petrecca [5] have recently extended the convexity theorem of Atiyah and Guillemin-Sternberg to Hamiltonian torus actions on conformal symplectic manifolds. The purpose of this paper is to generalize their result to the nonabelian case.…”
Section: Introductionmentioning
confidence: 99%